EFFECTIVENESS OF FOAM DRESSING VERSUS HYDROGEL DRESSING IN THE HEALING OF PRESSURE ULCERS AMONG ELDERLY PATIENTS IN INTENSIVE CARE UNITS OF A PUBLIC SECTOR TERTIARY CARE HOSPITAL IN ISLAMABAD: A QUASI-EXPERIMENTAL STUDY (Frontier in Medical and Health Research, 2026)
Background: Pressure ulcer (PUs) is a major concern among elderly patients due to immobility, reduced skin integrity, and comorbidities that impair wound healing. Selecting an effective dressing is essential to promote faster recovery, reduce infection risk, and improve patient comfort. Objective: The purpose of this study was to compare the efficacy of foam and hydrogel dressings in the healing of pressure ulcers in elderly patients attending a tertiary care centre.Methodology: A Quasi-experimental design was used to assess twenty elderly patients with pressure ulcers using Purposive non-probability sampling technique for selecting the participants, where ten participants was added to each group for comparison. Data were collected using the adapted PUSH scale and analysed using descriptive statistics in SPSS and Microsoft Excel. Ten patients received foam dressing (intervention group), while ten received hydrogel dressing (control group). Findings: Results revealed that foam dressing showed greater effectiveness than hydrogel dressing in healing pressure ulcers among elderly patients, with a higher mean PUSH score reduction (7.1 vs. 4.3). Furthermore, 70% of patients in the foam dressing group showed significant improvement compared to 30% in the hydrogel group.Conclusion: Foam dressing effectively accelerates pressure ulcer healing in elderly patients and should be incorporated into routine wound care practices, particularly in resource-limited healthcare settings.